The Impact of Psychoactive Substances on Fatal Traffic Accidents - Ozbilge, Ceyda Ergil; Deniz, Idris; Yukseloglu, Emel Hulya (Galenos Publ House, 2025)
Deaths due to road traffic accidents continue to represent a pressing global public health challenge. Reports from the World Health Organization and other international agencies indicate that millions sustain injuries and hundreds of thousands lose their lives annually due to traffic collisions. Most fatalities occur in nations with limited economic resources, where inadequate road infrastructure, limited use of seatbelts and helmets, disregard for speed limits, and the prevalence of operating a vehicle while impaired by alcohol or other psychoactive substances substantially increase the risk of death. In the investigation of fatal traffic accidents, postmortem examinations combined with systematic toxicological analyses are indispensable for clarifying accident mechanisms and informing the development of targeted preventive strategies.
Keywords: Fatal traffic accident; alcohol; psychoactive substance; toxicology; autopsy